Menoken, Shawnee County - Gonzalez, Nicholas (Kansas State University, The Chapman Center for Rural Studies, 2015)
This study explores what the town of Menoken, Menoken Township, Shawnee County, Kansas was like, and what happened to it. Menoken was eventually overtaken by bigger sister towns Topeka and Silver Lake. Methods include interviews, maps of the county, photographs of town site as it is today, and newspaper articles about the town.
Nicholas Gonzalez, “Menoken, Shawnee County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/164.
Keywords: Menoken Township; Rossville; Silver Lake; Shawnee County; Union Pacific; Kansas Pacific